Evaluation of Cell Therapy on Exercise Performance and Limb Perfusion in Peripheral Artery Disease: The CCTRN PACE Trial (Patients With Intermittent Claudication Injected With ALDH Bright Cells). Issue 15 (11th April 2017) - Perin, Emerson C.; Murphy, Michael P.; March, Keith L.; Bolli, Roberto; Loughran, John; Yang, Phillip C.; Leeper, Nicholas J.; Dalman, Ronald L.; Alexander, Jason; Henry, Timothy D.; Traverse, Jay H.; Pepine, Carl J.; et al.
Abstract : Background: Atherosclerotic peripheral artery disease affects 8% to 12% of Americans >65 years of age and is associated with a major decline in functional status, increased myocardial infarction and stroke rates, and increased risk of ischemic amputation. Current treatment strategies for claudication have limitations. PACE (Patients With Intermittent Claudication Injected With ALDH Bright Cells) is a National Heart, Lung, and Blood Institute–sponsored, randomized, double-blind, placebo-controlled, phase 2 exploratory clinical trial designed to assess the safety and efficacy of autologous bone marrow–derived aldehyde dehydrogenase bright (ALDHbr) cells in patients with peripheral artery disease and to explore associated claudication physiological mechanisms. Methods: All participants, randomized 1:1 to receive ALDHbr cells or placebo, underwent bone marrow aspiration and isolation of ALDHbr cells, followed by 10 injections into the thigh and calf of the index leg. The coprimary end points were change from baseline to 6 months in peak walking time (PWT), collateral count, peak hyperemic popliteal flow, and capillary perfusion measured by magnetic resonance imaging, as well as safety. Results: A total of 82 patients with claudication and infrainguinal peripheral artery disease were randomized at 9 sites, of whom 78 had analyzable data (57 male, 21 female patients; mean age, 66±9 years). The mean±SEM differences in the change over 6 months between study groups for PWT (0.9±0.8 minutes; 95% confidence interval [CI] −0.6 to 2.5; P =0.238), collateral count (0.9±0.6 arteries; 95% CI, −0.2 to 2.1; P=0.116), peak hyperemic popliteal flow (0.0±0.4 mL/s; 95% CI, −0.8 to 0.8; P =0.978), and capillary perfusion (−0.2±0.6%; 95% CI, −1.3 to 0.9; P=0.752) were not significant. In addition, there were no significant differences for the secondary end points, including quality-of-life measures. There were no adverse safety outcomes. Correlative relationships between magnetic resonance imaging measures and PWT were not significant. A post hoc exploratory analysis suggested that ALDHbr cell administration might be associated with an increase in the number of collateral arteries (1.5±0.7; 95% CI, 0.1–2.9; P =0.047) in participants with completely occluded femoral arteries. Conclusions: ALDHbr cell administration did not improve PWT or magnetic resonance outcomes, and the changes in PWT were not associated with the anatomic or physiological magnetic resonance imaging end points. Future peripheral artery disease cell therapy investigational trial design may be informed by new anatomic and perfusion insights. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01774097. Abstract : Supplemental Digital Content is available in the text.